E-atlas Fotografi Anatomi Akar, Batang dan Daun Tumbuhan Familia Arecaceae Sebagai Sumber Belajar - Fauzia, Syifa; Syamsiah, Syamsiah; Karim, Hilda (Jurnal Biotek, 2024)
E-Atlas of Plant Anatomy Photography Family Arcaceae is a learning resource that helps students in their learning process. The purpose of this study is to make e-Atlas an effective learning resource on Class XI Plant Tissue material in Senior High School / MA. Product development begins with the preparation of preserved specimens and fresh specimens on the underside of leaves by paraffin sectioning method. I then developed the E-Atlas design using the Canva application and further developed it into electronics using Anyflip. Research and Development (R&D) was chosen as the research design. R & D is a 40D development model that has four stages, namely, define, design, develop, and disseminate. The results showed that the e-Atlas of plant anatomy photography of the family Arecaceae as a learning resource was declared valid by expert validators with a validity level of 4.1. It can be concluded that the e-Atlas of anatomical photography of plants of the family Arecaceae is valid.